Bowel dysfunctions after acquired brain injury: a scoping review - Zandalasini, Matteo; Pelizzari, Laura; Ciardi, Gianluca; Giraudo, Donatella; Guasconi, Massimo; Paravati, Stefano; Lamberti, Gianfranco; Frizziero, Antonio (Frontiers in Human Neuroscience, 2023)
Bowel dysfunction is a common consequence of neurological diseases and has a major impact on the dignity and quality of life of patients. Evidence on neurogenic bowel is focused on spinal cord injury and multiple sclerosis; few studies have focused on patients with acquired brain injury (ABI). Neurogenic bowel dysfunction is related to a lifelong condition derived from central neurological disease, which further increases disability and social deprivation. The manifestations of neurogenic bowel dysfunction include fecal incontinence and constipation. Almost two out of three patients with central nervous system disorder have bowel impairment. This scoping review aims to comprehend the extent and type of evidence on bowel dysfunction after ABI and present conservative treatment. For this scoping review, the PCC (population, concept, and context) framework was used: patients with ABI and bowel dysfunction; evaluation and treatment; and intensive/extensive rehabilitation path. Ten full-text articles were included in the review. Oral laxatives are the most common treatment. The Functional Independence Measure (FIM) subscale is the most common scale used to assess neurogenic bowel disease (60%), followed by the Rome II and III criteria, and the colon transit time is used to test for constipation; however, no instrumental methods have been used for incontinence.